MEMBANGUN APLIKASI ERTUTUR DALAM ADAT KARO BERBASIS ANDROID - Denny Hasmita Sembiring Maha; Yunus Surakti (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2017)
Technology participates in the modernization of the delivery of information quite well, with the technology expected to assist in various aspects, especially karo tribe information and ertutur / seek kinship relationships to the special community karo community itself. Because many people karo not know anymore how to talk to relatives and riends, then created an application that helps find and inform the said owned. The application used in building this karo ertutur application is eclipse which is a java / android development application, eclipse has a plugin that can create an android based project. The results obtained from this application is a speech that is owned by others and also information about the karo tribe. The results achieved from this research is the completion of building applications ertutur in Android-based custom karo is expected to instill cultural insight Karo region